Acute liver abscess after non-operative management of blunt liver injury: A rare case managed with laparoscopic drainage. (2020) - Lin, Mu-Yun; Liao, Ching-Yun; Lin, Being-Chuan
Highlights: Non-operative management (NOM) has today become the first treatment of choice when possible in patients with blunt liver injury. Liver abscess as a complication after NOM of blunt liver injury is a rare entity, with an incidence rate of 1.5%. The most common bacteria responsible for liver abscess include Klebsiella pneumoniae, Staphylococcus aureus, Streptococcus pyogenes, gram-positive cocci, Clostridium, and mixed organisms. Laparoscopic drainage can be performed safely and effectively for the liver abscess. Abstract: Introduction: Liver abscess may develop as a rare complication of the non-operative management (NOM) of blunt liver injury. Presentation: A 36-year-old male was injured in a motorcycle accident on November 28, 2017. First aid was performed at the local hospital, then he was transferred to our trauma center for further management. The abdominal computed tomography (CT) revealed a segment 7/8 liver laceration, and the liver injury was of grade III according to the American Association for the Surgery of Trauma-Organ Injury Scale for liver injury. Intermittent high fever was observed for the first 3 days after NOM, and repeat abdominal CT showed an abscess with rupture at the previously injured liver parenchyma. He underwent laparoscopic drainage of the liver abscess, and culture revealed the presence of Salmonella enterica, serogroup D. After laparoscopic drainage, the patient recovered well, with a 21-day hospital stay. Discussion: Liver abscess as a complication after NOM of blunt liver injury is a rare entity, with an incidence rate of 1.5%. It is usually seen in major liver injuries (grade III and above) and the abscesses take a median of 6 days (range, 1–12 days) to form and be diagnosed. The management of liver abscess may be by surgical drainage (laparotomy or laparoscopy) or percutaneous drainage. Conclusion: This report reminds us the liver abscess complication after NOM of blunt liver injury, although it is a rare entity. Results of this patient support drainage of the liver abscess can be safely and effectively performed by laparoscopy.